Risk factors for malignancy in pediatric subacute/chronic focal craniocervical lymphadenopathy - Haimi-Cohen, Yishai; Elron, Eyal; Oz-Alcalay, Lital; Hejly, Lama; Hod, Roy; Ashkenazi-Hoffnung, Liat (Frontiers in Pediatrics, 2025)
AimsTo describe the factors associated with malignancy in otherwise healthy children with focal persistent isolated craniocervical lymphadenopathy at low risk for malignancy, in order to aid in decisions of nodal surgical excision.Material and methodsDemographic and clinical data were retrospectively obtained for children with subacute and chronic craniocervical lymphadenopathy, treated from January 2008 to December 2020 at a general pediatric ambulatory clinic of a tertiary center. Univariate and multivariate analyses of risk factors for malignancy were performed.ResultsOf the 450 children included, median age 4.2 years (interquartile age: 2.4–8.7), 25 (5.6%) were eventually diagnosed with a malignancy. In univariate analysis, factors associated with malignancy included older age, increased nodal size, location (supraclavicular and lateral cervical), systemic signs such as decreased appetite and weight loss, and abnormal imaging studies. Referral by an ear, nose, throat specialist vs. a family physician or a pediatrician was also associated with malignancy. Fever, night sweats, pruritus, hepatosplenomegaly and laboratory workup were not associated with malignancy. Twenty percent of the children older than 12.5 years and 12% of those with a lymph node diameter >31 mm were diagnosed with malignancy. Multivariate analysis showed associations with malignancy of older age and larger lymph nodes; the respective odds ratios were 1.649 (95%CI: 1.197–2.349, p = 0.004) for every 3 years and 2.080 (95%CI: 1.292–3.330, p = 0.002) for every one centimeter.ConclusionsOlder age and increased nodal size can help identify children with focal craniocervical lymphadenopathy who are at increased risk for malignancy and for whom surgical intervention should be strongly considered.